Beforehand Enquiry About Health Care Practitioners and Delivery Places Among the General Population in A Rural District in An Indian Southern State- An Exploratory Factor Analysis - George, Neethu; Dharmaraj, Rock Britto; Arasukumar, Aswin; Ekambaram, Gokul Krishna; Jesupaul Thangaraj, Gifty Miracline; Ravisubramanian, Gokul; Perundalaiyur Chandran, Gayathri devi; Prabhakaran, Gomathy Manju (National Journal of Community Medicine, 2024)
Background: In recent years, many countries have embraced demand-driven healthcare systems, emphasizing patient choice and pre-enquiry in selecting healthcare providers. The purpose is to assess the occurrence and factors influencing beforehand enquiry of the general rural population regarding the health care practitioners and delivery places Materials and methods: The study was a cross-sectional survey conducted over 2 months among 1100 participants in Perambalur district, Tamil Nadu. The study utilized a questionnaire gathering sociodemographic data and 20 questions about healthcare enquiries, including place/person of enquiry, information source, enquiry characteristics, and reliability. Bivariate analysis identified significant predictor variables, while principal component analysis with Varimax rotation determined core factors. Results: The study found that 68.8% of participants (757 individuals) enquired about healthcare facilities and professionals before visiting. Core factors influencing these enquiries included healthcare professionals, hospitals, subjects, and cost concerns. Enquiries about healthcare places were mainly influenced by discussions with relatives, travel issues, and costs. Regarding healthcare professionals, characteristics such as communication skills, physician quality, previous patient experiences, and costs played significant roles in pre-enquiries. Conclusion: Patient enquiries are influenced by diverse factors and may not always be rational. Providing truthful information is crucial to support informed decision-making in healthcare.